The politics of bureaucracy An introduction to comparative public administration - Peters, B. Guy (Routledge, 2018)
Written by B. Guy Peters, a leading authority in the field, this comprehensive exploration of the political and policy making roles of public bureaucracies is now available in a fully revised seventh edition, offering extensive, well-documented comparative analysis of the effects of politics on bureaucracy.